Backlash : libel, impeachment, and populism in the reign of Queen Anne - Carnell, Rachel (University of Virginia Press, 2020)
"Rachel Carnell tells the story of a backlash against decades of increasingly progressive government in Britain after the Glorious Revolution of 1688. The book relates the arrest of a Tory political satirist and Whigs' impeachment of a High Church clergyman and the resulting backlash, with mobs surging the streets. Queen Anne dissolved Parliament, and the new elections brought in a Tory majority who swiftly passed reactionary legislation"--